Inter cell interference mitigation technique in femtocell and macrocell in LTE system - Reza, Asif; Raisa, Farah; Abdullah, Khaizuran (IEEE, 2017)
To handle huge data traffic in networks, deployment of femtocell and macrocell in Long Term Evolution (LTE) is the future of the network society. The efficiency of the system is increased. However, the system deployment may yield to major issue such as the inter cell interference with their neighboring cells. The effect of this issue is the occurrence of low quality of service. One of the proposed mitigations is to introduce the new circuitry connections. Other literatures are still going on mitigation techniques which have some positive and negative drawbacks. In this paper, the interference mitigation techniques including reviewing the strengths and weakness are discussed.